Survey of Students’ Perceptions Toward Teacher Feedback in ESP Chemistry Courses - Muhamad Syahrul Mubarok; Indri Yulianti; Wahyu Nengsi (EDUCATION JOURNAL OF INDONESIA, 2025)
Teacher feedback plays a crucial role in supporting students’ learning development, particularly in English for Specific Purposes (ESP) Chemistry, where learners must master both linguistic and scientific competencies. This study investigates Chemistry students’ perceptions of teacher feedback, the types of feedback they consider most beneficial, and the influence of feedback on their motivation and engagement. Using a mixed-method design, quantitative data were collected from 100 undergraduate Chemistry students through a Likert-scale survey, while qualitative insights were obtained from interviews with 3–5 selected participants. Findings indicate that students generally hold positive perceptions of teacher feedback, valuing clarity, specificity, and constructive tone. They consider timely and detailed feedback particularly helpful for improving language accuracy, content comprehension, and academic performance. However, students also report inconsistency in feedback quality and a lack of follow-up explanations in some instances. The study highlights the need for balanced feedback addressing both linguistic and disciplinary aspects, and emphasizes the importance of teacher feedback literacy in ensuring effective and meaningful feedback practices. These findings provide insights for improving ESP Chemistry instruction and enhancing students’ learning outcomes. Keywords: ESP Chemistry, Learning Motivation, Student Perception, Teacher Feedback.